Calamity or Catalyst : Futures for Community in Twenty-First-Century Crime Prevention - Carson, Wesley G. (The British journal of criminology, 2007)
This paper will discuss the potentially explosive exclusionary potential associated with the use of unreflexive communalism in crime prevention at a time at which inequality, marginalization, racialization and othering' are becoming increasingly salient social issues. The paper will then explore how the communal might be rescued or re-imagined to avoid such risks and, just possibly, to generate a more progressive form of crime prevention - one more attuned to the realities of changing patterns of governance. In this context, the place of human obligations and rights in communal crime prevention will be discussed, particularly with regard to democratic participation and respect. Therein, it will be suggested, there is at least the potential for a more optimistic and less calamitous future for community oriented crime prevention